2018
DOI: 10.1039/c7tc05593e
|View full text |Cite
|
Sign up to set email alerts
|

Color-tunable luminescent hydrogels with tough mechanical strength and self-healing ability

Abstract: A series of robust, color-tunable and self-healing luminescent hydrogels were constructed via self-assembly strategy driven by the electrostatic interaction of positively-charged luminescent micelles consisting of lanthanide complexes and negatively-charged clay nanosheets in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…The peaks at 580, 592, 612, 651 and 700 nm correspond to 5 D 0 -7 F 0 , 5 D 0 -7 F 1 , 5 D 0 -7 F 2 , 5 D 0 -7 F 3 and 5 D 0 -7 F 4 transitions of Eu 3+ , respectively. 25 The peak at 612 nm is responsible for the red emission color, which corresponds to the red we see in Fig. 3.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The peaks at 580, 592, 612, 651 and 700 nm correspond to 5 D 0 -7 F 0 , 5 D 0 -7 F 1 , 5 D 0 -7 F 2 , 5 D 0 -7 F 3 and 5 D 0 -7 F 4 transitions of Eu 3+ , respectively. 25 The peak at 612 nm is responsible for the red emission color, which corresponds to the red we see in Fig. 3.…”
Section: Resultsmentioning
confidence: 79%
“…As we all know that the luminescence of rare earth complexes is mainly due to the "antenna effect" between ligands and central ions, the excited triplet state of ligands is very important for their luminescent intensity. [24][25] The excited triplet states of organic ligands correspond to phosphorescent emission, so the length of phosphorescence lifetime can be used as an important index to judge the energy of excited triplet states of ligands. According to Yan et al the report, [30] the distance of π-π stacking of ligands can affect can affect their respective excited triplets and their phosphorescence lifetimes.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the corrosive medium would be in contact with the substrate directly and corrode from spot to surface in the long term. Therefore, self-healing coatings have catched a lot of attention for their autonomically repairment [15][16][17][18][19] and preventing the substrate from corrosion. [20][21][22] It is reported that the prerequisite for self-healing of damage is the generation of a mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…Researches on organic-inorganic hybrid materials have been thriving over the past few years because these materials combined the structural, physical and chemical properties of both inorganic host materials and organic guest species 13 . Intercalation reaction of natural layered minerals is a well-known method for preparing hybrid materials in a nanoscale 46 .…”
Section: Introductionmentioning
confidence: 99%